2019
DOI: 10.1016/j.bbr.2019.112063
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural response to visual perspective and body size in the extrastriate body area

Abstract: Neuroimaging research has independently implicated the extrastriate body area (EBA) in distinguishing between different visual perspectives and morphologies of bodies within visual processing. However, the combined processing of these physical attributes towards neural EBA response remains unclear, and may be crucial in influencing higher-order, aesthetic evaluation of bodies. Indeed, EBA alterations amongst eating disorder patients have been associated with disturbances in body image, and disruption 8 to EBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 77 publications
0
17
1
Order By: Relevance
“…Another alternative that must be studied further is that what is actually viewed by the participants in the allocentric and egocentric perspectives differs also in terms of body parts, of potential aesthetics qualities, and brain mechanisms, allowing the identification of body parts. Carey et al [ 65 ] studied the role of a cortical region dedicated to the visual processing of bodies and body parts. Their results suggested that the extrastriata body area was activated differentially in the allocentric and egocentric perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative that must be studied further is that what is actually viewed by the participants in the allocentric and egocentric perspectives differs also in terms of body parts, of potential aesthetics qualities, and brain mechanisms, allowing the identification of body parts. Carey et al [ 65 ] studied the role of a cortical region dedicated to the visual processing of bodies and body parts. Their results suggested that the extrastriata body area was activated differentially in the allocentric and egocentric perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectations, participants with BED were not characterized by aberrant activation in the EBA in response to the own body, which suggests that the EBA does not play a specific role in body image disturbances in BED. Notably, previous findings on the role of the FBA and the EBA in body processing in eating disorders (AN and BN) have been quite inconsistent across studies (Carey et al, 2019; Castellini et al, 2013; Miyake et al, 2010; Suda et al, 2013; Uher et al, 2005; Vocks et al, 2010). Relative to these previous studies, the present study differed in several ways: First, we used a localizer task to individually identify the EBA and FBA.…”
Section: Discussionmentioning
confidence: 96%
“…2A). EBA computations are thought to discriminate between bodily attributes and parts (Carey et al, 2019) and provide postural information to frontoparietal regions (Zimmermann et al, 2018), indicating a pivotal role in action planning. The FBA is thought to process images of whole bodies (Taylor et al, 2007) and pairs of body parts (Bratch et al, 2018).…”
Section: Distributed Processes Contribute To Body Category Selectivitymentioning
confidence: 99%
“…Processing of human body images (Fig 4A) is associated with the fusiform body area (FBA) and the extrastriate body area (EBA) [2,3,71], which are located in the lateral occipito-temporal cortex (Tables 1 and 2, Fig 4B). EBA computations are thought to discriminate between bodily attributes and parts [153] and provide postural information to frontoparietal regions [72], indicating a pivotal role in action planning. The FBA is thought to process images of whole bodies [3] and pairs of body parts [154].…”
Section: Distributed Activity Flowing Over Intrinsic Connectivity Gen...mentioning
confidence: 99%